Modulating fracture toughness through processing-mediated mesostructure in additively manufactured Al-12Si alloy - Jamshidian, Mostafa (2022)
Al-12Si alloy processed through additive manufacturing exhibits a complex hierarchical structure. At the mesoscale, its melt pool boundaries constitute a network of weak interfaces that provides preferred pathways for crack kinking, leading to both marked anisotropy and apparent enhancement in the fracture energy. In this study, a multiscale cohesive zone-based computational model and a semi-analytical approach for kinked cracks are used to investigate the effect of melt pool configuration on fracture energy enhancement and anisotropy due to crack path tortuosity. We experimentally validate our methodology using fracture toughness testing of compact tension specimens, then systematically study the simultaneous effects of hatch spacing, layer thickness, and crack surface orientation on variations of the fracture energy. While the fracture energy increases with increasing hatch spacing and decreasing layer thickness, processing defects such as keyholing give practical limits to the melt pool geometry, limiting the fracture energy enhancement. We found that the fracture energy can be enhanced as high as a factor of two with an optimal crack surface orientation that is linearly proportional to the ratio of hatch spacing to layer thickness and varies between 60° and 100°.